Environmental Health Risk Analysis of Exposure to Iron (Fe) and Manganese (Mn) in Dug Well Water in Banta-Bantaeng Sub-district, Makassar City - Aprilyani Amri, A. Jihan Asyura; Mallongi, Anwar; Ibrahim, Erniwati; Kasim, Setiawan (Journal of Neonatal Surgery, 2025)
Clean water is one of the most important necessities of life it can be a primary means to improve public health. The purpose of this study was to analyze the health risks of exposure to iron (Fe) and manganese (Mn) in dug well water in Banta-Bantaeng Village, Makassar City. This study is an observational study with environmental health risk analysis (EHRA). The results showed that the level of risk of exposure to heavy metal iron for adults was 3 x 103 ml/L/day while for children it was 9 x 102 ml/L/day, which means that on average the community around the Banta-Bantaeng Village Area, Makassar City is at risk of experiencing health problems in children and adults because the THQ value is > 1. For the risk level of exposure to heavy metals manganese, the average for adults is 2 x 105 ml/L/day while for children it is 2 x 102 ml/L/day, which means that on average, the community around the Banta-Bantaeng Village Area, Makassar City is at risk of experiencing health problems in children and adults because the THQ value is > 1. The average level of health risk of exposure to iron (Fe) and manganese (Mn) in dug well water in Banta-Bantaeng Village, Makassar City, is at risk for health.